Employee Perceptions of the Effectiveness of Diversity Management in the Australian Public Service: Rhetoric and Reality. (December 2014) - Soldan, Zhanna; Nankervis, Alan
The changing demographics of Australian society and its workforce have propelled Australian Public Service (APS) organizations to proactively engage in diversity management (DM). Despite this growing imperative for DM in the APS, there has been little inquiry into the effectiveness of such programs. The aim was to investigate how an APS agency was transforming its commitment to DM into action. The findings revealed that a significant gap exists between the rhetoric of what the DM policy seeks to achieve and the reality experienced by employees in the areas of targeted recruitment, employee retention, and employee development. The practical implications of findings for wider stakeholders responsible for designing and implementing DM are discussed and limitations are noted together with recommendations for future research.